The Effect of Providing Information on Sputum Collection Techniques on The Quality of Sputum for Acid-Fast Bacilli Examination - Usdiyanto, Usdiyanto; Fauzi, Fadilah Hamzah; Alam, Misika (Jurnal Ilmu Kesehatan (JIKSAN), 2025)
Background: Tuberculosis (TB) is an infectious disease caused by the bacteria Mycobacterium tuberculosis. TB most often attacks the lungs (pulmonary TB), but can also affect other organs such as the kidneys, bones and brain (extra-pulmonary TB). This disease is characterized by the formation of granulomas (small masses of immune cells) in infected tissue. TB is transmitted through the air and can be serious if left untreated, especially in individuals with weakened immune systems. Purpose: The aim of this research is to determine the effect of providing information about how to phlegm on the quality and volume of phlegm. Method: The method used in this research was Quasi Experimental with one treatment (one-group pretest-posttest design). Result: The results of the research from 30 sputum samples suspected of TB at the Karawang Kulon Community Health Center, the results from before being given information on the quality of sputum samples which did not meet the requirements for examination were 29 and after being given information on the quality of sputum which met the examination requirements were 28. The results from before being given information on the volume of sputum samples those who did not meet the examination requirements were 28 and after being given information on the volume of sputum that met the requirements for examination, the number was 28. From the results of the Wilcoxon test, the Asym value was obtained. Sig. (2-tailed) 0.000 < significant value 0.05. So, it can be concluded that there is a significant influence on providing information about how to sputum on the quality of phlegm for checking acid-fast bacteria at the Karawang Kulon Community Health Center.